Down-regulation of murine beta-defensin-2 in Lewis lung carcinoma cells results in accelerated growth of tumor cells in vitro and in vivo - Zhuravel, E.; Shestakova, T.; Glushko, N.; Soldatkina, M.; Pogrebnoy, P. (Experimental Oncology, 2008)
To evaluate the anti-tumor activity of murine beta-defensin-2 (mBD-2) expression in vitro and in vivo. Materials and Methods: Based on pcDNA3 vector, constructs containing mBD-2 cDNA coding mature defensin molecule (pcDNA3-mBD2), and Igk-mBD-2 insertion, coding secretory sequence plus mature defensin molecule (pcDNA3-Igk-mBD-2) were generated. Lewis lung carcinoma (3LL) cells were transfected in vitro with these plasmids and with blank pcDNA3 vector, and the proliferative rate and clonogenic ability of obtained cell lines cultivated in vitro were analyzed using 3H-incorporation technique and colony formation in semi-soft medium, respectively. Expression of mBD-2 mRNA was studied by semiquantative RT-PCR analysis. Also, transfected cells were transplanted to C57B mice, and the patterns of tumor growth in vivo were analyzed by routine techniques. Results: We have found out that in the 3LL cells transfected with pcDNA3-mBD-2 and pcDNA3-Igk-mBD-2, the expression of mBD-2 mRNA is significantly down regulated compared to wild-type cells and 3LL cells transfected with blank vector. The cells with suppressed mBD-2 expression differed from parental cells and cells transfected with blank vector by higher proliferation rate (p < 0.001) and higher clonogenic ability. The 3LL-mBD-2 and 3LL-Igk-mBD-2 cells that are transplanted to C57B mice gave rise to more aggressive tumors that possessed significantly higher growth rate (p < 0.01) than those that arise from wild-type 3LL cells. Conclusion: The obtained results are evidencing on a possible tumor-suppressing role of mBD-2 expression.